Etiology of bacterial diseases of young walnut trees in Serbia - Iličić, Renata; Bagi, Ferenc; Blagojević, Milan; Gošić, Jovica; Milovanović, Predrag; Popović, Tatjana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
In the summer and autumn of 2019-2020, young walnut orchards were monitored for the presence of bacterial diseases. Diseased walnut samples comprising trunks and branches with symptoms of vertical oozing canker (VOC), walnut bacterial blight (WBB) and superficial bark necrosis were collected from eight locations in Serbia. Based on phenotypic features, pathogenicity, and molecular assays using PCR with specific primers, 49 isolates obtained from samples showing VOC and WBB symptoms were identified as Xanthomonas arboricola pv. juglandis, while further two isolates obtained from bark necrosis were identified as Brenneria rubrifaciens. One tested X. a. pv. juglandis isolate obtained from a VOC sample produced deep cankers in the bark of inoculated trunks of young walnut trees (cultivars Chandler, Franquette and Šejnovo). Therefore, this is the first report of an association between X. a. pv. juglandis and VOC symptom in Serbia. Considering that X. a. pv. juglandis significantly endangers walnut production, the presence of this pathogenin walnut transplant imports needs to be assessed by an authorised laboratory. Furthermore, as this is also the first report of B. rubrifaciens on walnut trees in Serbia, it is noteworthy that this pathogen is not  particularly harmful to young walnut trees.
Keywords: walnut; phytopathogenic bacteria; vertical oozing canker; pathogen identification